2006
DOI: 10.1111/j.1530-9134.2006.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Publications in an R&D Race

Abstract: This paper considers a multistage dynamic R&D race in which the competitors strategically publish research findings. Publications change the prior art, thus affecting patentability. Firms publish when they are behind in the race and their rival is close to winning it. Publication sets back both competitors and gives the follower a chance to catch up. Publications prolong the race. Firms are more likely to publish the more patient they are, and the higher their probability of success. Asymmetry between the firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…There is a strategic motivation to disclose inventions for the simple reason that it generates prior art: it makes knowledge advances public and not patentable, limiting the possibilities for rivals to patent inventions related to the disclosed information. Theory explains that disclosure extends the patent race (Baker and Mezzetti, 2005;Bar, 2006) which raises the costs of competing (making some firms get out of the race) but allows firms to gain time until a breakthrough discovery is made. It can then be attractive for both leaders and follower companies and will depend on specific circumstances; how far the lagging firm is in the race; the asymmetry between firms in investment costs, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a strategic motivation to disclose inventions for the simple reason that it generates prior art: it makes knowledge advances public and not patentable, limiting the possibilities for rivals to patent inventions related to the disclosed information. Theory explains that disclosure extends the patent race (Baker and Mezzetti, 2005;Bar, 2006) which raises the costs of competing (making some firms get out of the race) but allows firms to gain time until a breakthrough discovery is made. It can then be attractive for both leaders and follower companies and will depend on specific circumstances; how far the lagging firm is in the race; the asymmetry between firms in investment costs, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies have shown that defensive publishing may be used by firms to extend the patent race because it can help gain time by raising the patentability threshold and thus delay patent filings until further research is done (Baker and Mezzetti, 2005;Bar, 2006). For a firm trailing behind, a longer race might offer an opportunity to catch up, while for a leading firm, extending the race raises the costs of competing, which will in certain circumstances discourage the laggard from racing so aggressively (Baker and Mezzetti, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first branch, mainly carried out by economists, sees open disclosure of technological advances as a catching up strategy for laggards in patent races. In these models the laggard publishes preliminary results that are not patentable in order to prolong the patent race (Parchomovsky, 2000, Baker and Mezzetti, 2005, Bar, 2006, Lichtmann et al, 2000, De Fraja, 1993. Scholars in law and management science, on the contrary, consider open disclosure as a complementary strategy to patenting (Colson, 2001, Buxbaum, 2001, Rinner, 2003, Johnson, 2004, Henkel and Pangerls, 2008.…”
Section: Resultsmentioning
confidence: 99%
“…Economic scholars have analyzed defensive publishing in the context of patent race models (Parchomovsky, 2000, Baker and Mezzetti, 2005, Bar, 2006, Lichtmann et al, 2000, De Fraja, 1993. Patent race models typically consider two inventors that compete for being first to complete and patent a specific invention.…”
Section: Introductionmentioning
confidence: 99%